The Information and Communication (ICT) Strategic Planning for Perlis State Government - Siti Hasnah, Abu Hasan Shaari (2006)

(untitled)
Information and Communication Technology (ICT) is an increasingly powerful tool for improving the delivery of government services, enhancing ICT development opportunities and participating in global markets. Proper planning must be done in order to get a technology plan that can be used to help identify and priorities the applications that are needed for the state. Using the methodology that was published by MAMPU as a guidance for the state government to develop their own Information and Communication (ISP) Strategic Planning, this thesis is to develop an ISP for the Perlis State Government. With the help of this methodology the study focus on identifying the current ICT environment and to propose the new ICT environment to enhancing the usage of ICT technology in order to perform their task in the Perlis State Government Administration. Hopefully this ISP can give a valuable information and as a guidance in ICT development and implementation for the Perlis State Government.